PERKEMBANGAN GERAK : KELENTUKAN (FLEXYBILITY) - Suharti, Suharti (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2016)
The person's eligibility will provide the convenience and comfort of a person in performing various movements. Every movement, both in daily activities and in sports, largely demands a good body shape factor. Abstinence or flexibility is a necessary requirement for on going motion for humans. Movements are displayed more harmonious and rhythmic if supported by good body shape. The development of a person's body is affected by age. From a small person's body shape will develop until the age of teens (puberty). In adolescence the development of formation is relatively fixed, because it has reached its peak. Furthermore, in general will decrease with age.